2021
DOI: 10.3389/fgene.2021.652632
|View full text |Cite
|
Sign up to set email alerts
|

Systems Toxicology Approach for Assessing Developmental Neurotoxicity in Larval Zebrafish

Abstract: Adverse outcomes that result from chemical toxicity are rarely caused by dysregulation of individual proteins; rather, they are often caused by system-level perturbations in networks of molecular events. To fully understand the mechanisms of toxicity, it is necessary to recognize the interactions of molecules, pathways, and biological processes within these networks. The developing brain is a prime example of an extremely complex network, which makes developmental neurotoxicity one of the most challenging area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 102 publications
(115 reference statements)
0
6
0
Order By: Relevance
“…For example, an integrative analysis using CTD, SSC, and ASC revealed a total of 212 gene–environment interaction pairs putatively relevant for ASD, and provided a list of candidate genes susceptible to chemicals associated with ASD, such as valproic acid, benzo(a)pyrene, bisphenol A, particulate matter, and perfluorooctane sulfonic acid ( Santos et al, 2019 ). A novel in silico approach using GEO identified tumor suppressors: p53, retinoblastoma 1, and Kr ü ppel-like factor 8 as leading nodes in the network of developmental neurotoxicity of selective serotonin reuptake inhibitors and antidepressants associated with ASD ( Li et al, 2021 ). A study using CTD and a database of ASD gene networks ( Nelson et al, 2012 ) found that ASD-associated genes are selectively targeted by environmental pollutants such as pesticides, heavy metals, and phthalates ( Carter and Blizard, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, an integrative analysis using CTD, SSC, and ASC revealed a total of 212 gene–environment interaction pairs putatively relevant for ASD, and provided a list of candidate genes susceptible to chemicals associated with ASD, such as valproic acid, benzo(a)pyrene, bisphenol A, particulate matter, and perfluorooctane sulfonic acid ( Santos et al, 2019 ). A novel in silico approach using GEO identified tumor suppressors: p53, retinoblastoma 1, and Kr ü ppel-like factor 8 as leading nodes in the network of developmental neurotoxicity of selective serotonin reuptake inhibitors and antidepressants associated with ASD ( Li et al, 2021 ). A study using CTD and a database of ASD gene networks ( Nelson et al, 2012 ) found that ASD-associated genes are selectively targeted by environmental pollutants such as pesticides, heavy metals, and phthalates ( Carter and Blizard, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…We have developed a semi-automatic pipeline and scripts that take a CTN in BEL format, remove unneeded node and connection annotations and add new functional ones, then reduce the network to a size similar to an AOP network ( Pollesch et al, 2019 ). We performed these operations on a recently developed zebrafish developmental neurotoxicity network as a case study ( Li et al, 2021 ). The network was then separated into subnetworks, based on different starting points (candidate MIEs of different types) and endpoints (pathologies), with a size suitable for close visual inspection.…”
Section: Discussionmentioning
confidence: 99%
“…The zebrafish causal developmental neurotoxicity network, which is the basis of our AOP development, has been developed in an earlier publication, therefore we here only summarize the most relevant properties of the network for this study, and refer the reader to original publication for details ( Li et al, 2021 ). CTN network development usually starts from a known adverse outcome of interest.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Reverse causal reasoning is a method used to support the construction of computational models to help evaluate and predict chemical toxicity. 36,37 Therefore, this approach falls in line with the current push towards more computationally based toxicity assessments. 38 By applying a systems biology approach to our brain-tissue-specific molecular dataset, it was possible to identify potential gene biomarkers that were significantly correlated with exposure to WWTP effluent and with neurologically relevant functions and disease states.…”
Section: Introductionmentioning
confidence: 89%